Surgical Treatment for Primary Lymphedema: A Systematic Review of the Literature - Gaxiola-García, Miguel Angel; Escandón, Joseph M.; Manrique, Oscar J.; Skinner, Kristin A.; Kushida-Contreras, Beatriz Hatsue (Archives of Plastic Surgery, 2024)
This is a retrospective review of surgical management for primary lymphedema.Data were extracted from 55 articles from PubMed MEDLINE, Web of Science, SCOPUS, and Cochrane Central Register of Controlled Trials between the database inception and December 2022 to evaluate the outcomes of lymphaticovenous anastomosis (LVA) and vascularized lymph node transfer (VLNT), and outcomes of soft tissue extirpative procedures such as suction-assisted lipectomy (SAL) and extensive soft tissue excision.Data from 485 patients were compiled; these were treated with LVA (n = 177), VLNT (n = 82), SAL (n = 102), and excisional procedures (n = 124). Improvement of the lower extremity lymphedema index, the quality of life (QoL), and lymphedema symptoms were reported in most studies. LVA and VLNT led to symptomatic relief and improved QoL, reaching up to 90 and 61% average circumference reduction, respectively. Cellulitis reduction was reported in 25 and 40% of LVA and VLNT papers, respectively. The extirpative procedures, used mainly in patients with advanced disease, also led to clinical improvement from the volume reduction, as well as reduced incidence of cellulitis, although with poor cosmetic results; 87.5% of these reports recommended postoperative compression garments. The overall complication rates were 1% for LVA, 13% for VLNT, 11% for SAL, and 46% for extirpative procedures. Altogether, only one paper lacked some kind of improvement.Primary lymphedema is amenable to surgical treatment; the currently performed procedures have effectively improved symptoms and QoL in this population. Complication rates are related to the invasiveness of the chosen procedure.
Keywords: lymphedema; primary lymphedema; congenital lymphedema; lymphovenous anastomosis; lymph node transplant